Design, Integration, And Deployment Of A Flutter–Firebase Mobile Commerce Application At Berlian Tech - Labib Falah Athallah; Ahmad Habib; Geri Kusnanto (Yayasan Inovasi Kemajuan Intelektual, 2024)
The development of e-commerce in Indonesia has shown an upward trend, with gross merchandise value (GMV) reaching USD 59 billion in 2022. This study aims to develop a mobile-based e-commerce application, with a case study of the Berlian Tech Online Store. This study employs a Research and Development (R&D) method using a software engineering approach based on the Software Development Life Cycle (SDLC) with the waterfall model. The waterfall model provides a sequential lifecycle approach, beginning with the analysis phase and proceeding to design, coding, testing, and maintenance. The requirements analysis is divided into two categories: functional requirements and non-functional requirements. The system architecture comprises four entities: authentication, products, and the shop. The software architecture adopts the Model-View-ViewModel (MVVM) pattern due to its superior CPU efficiency, with an average CPU usage of 8.92% and a memory consumption of 121.48 MB. The MVVM architecture is combined with a service layer and an API gateway. The Online Store application was successfully designed using the Model-View-ViewModel (MVVM) system architecture, combined with a service layer that facilitates communication between the API gateway and the view. The NoSQL database implemented with Firebase provides high flexibility for storing data in a non-relational structure. The results of black-box testing indicate that all core system features, including user authentication, product management, shopping cart, checkout, and transaction processing, function properly and align with user requirements.